2004
DOI: 10.1159/000082922
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features of Extranodal Lymphomas: Kuwait Experience

Abstract: A total of 935 patients with extranodal non-Hodgkin lymphoma (NHL) diagnosed in the period between January 1985 and December 2000 in Kuwait Cancer Center, serving the whole population of Kuwait, were used to describe the clinicopathological and epidemiological features of extranodal lymphomas in Kuwait. Extranodal lymphomas accounted for 45% of all NHL observed during this time. All NHL cases from Kuwait Cancer registry were analyzed and pathologically reclassified using the latest WHO (2000) classification. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
3
11
0
1
Order By: Relevance
“…Ten percent of gastric MALT lymphomas had history of H. pylori gastritis demonstrated by routine Giemsa staining. Studies from Middle East countries like Iraq (Yaqo et al, 2011) and Kuwait (Temmim et al, 2004) have reported higher incidence of intestinal localization of lymphomas, as these studies have reported more number of Burkitt lymphomas among pediatric patients which tend to occur more at these sites. Immunoproliferative small intestinal disease (IPSID), more commonly reported from the Middle East countries was observed in two young males (26 years, 34 years) with history of loose motion, and malabsorption.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Ten percent of gastric MALT lymphomas had history of H. pylori gastritis demonstrated by routine Giemsa staining. Studies from Middle East countries like Iraq (Yaqo et al, 2011) and Kuwait (Temmim et al, 2004) have reported higher incidence of intestinal localization of lymphomas, as these studies have reported more number of Burkitt lymphomas among pediatric patients which tend to occur more at these sites. Immunoproliferative small intestinal disease (IPSID), more commonly reported from the Middle East countries was observed in two young males (26 years, 34 years) with history of loose motion, and malabsorption.…”
Section: Discussionmentioning
confidence: 96%
“…Worse therapeutic outcome was seen for patients with lymphoma involving rare sites (Yun et al, 2010), those with T-cell phenotype (Ko et al, 2009), and among pediatric age group (Temmim et al, 2004). In another study, age, performance status, stage of disease, and serum LDH level were independent prognostic variables, whereas nodal or extra nodal site did not have any prognostic significance (Lal et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BL was the most common NHL subtype (69%) in our series. Furthermore, BL accounted for 78.2, 77.2, 68, 48.2, 42.2 and 39% of the cases in studies conducted in Brazil, Kuwait, Saudi Arabia, Germany, UK and Egypt, respectively (16,(21)(22)(23)(24)(25). By contrast, BL was encountered at a surprisingly low frequency (9-12%) in India, Pakistan and Shanghai (21,26).…”
Section: Discussionmentioning
confidence: 99%